The - dictionary; Gunhild Prowe; Jill Schneider; grammar; William Rowlinson (Oxford University Press, 2001)
This major new edition of a handy two-in-one reference to the German language offers a entirely new layout and design. Featuring over 100,000 words, phrases, and translations incorporating the German spelling reforms, as well as being completely revised and updated, it covers all the essential vocabulary of everyday life. In addition, frequently used words, which are the building blocks to learning the language, are given a special layout with usage notes throughout to help users employ them correctly. Special warning symbols new to this edition make slang and informal words and expressions instantly identifiable